A rare case of chickenpox induced myoclonus - Mathur, Navgeet; Mathur, Medha; Verma, Anjana (Nepal Journal of Neuroscience, 2021)
In presence of abnormal neurological features, infective etiology should be kept as one of the differential diagnoses. This case report was about 38 years old male patient who presented with fever with blister-like rashes in centripetal distribution over the body and myoclonus. CSF examination showed the presence of varicella-zoster Ig M antibodies. Diagnosis of chickenpox induced myoclonus was made. Appropriate treatment recovered the patient completely. This case report highlighted the clinical spectrum of chickenpox as well as the possible pathogenesis and diagnostic, therapeutic approach of this uncommon entity.